From Signs To Values: A Semiotic Psychopedagogical Analysis Of Mahllul Qiyam - Wirman Hardi Gunawan; Mohammad Fakhri (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study reconstructs the semiotic system embedded in the translated verses of Mahllul Qiyam and examines its psychopedagogical implications for values-based Indonesian language education. Existing scholarship reveals a critical gap: religious texts are predominantly treated as literary or cultural artifacts, with limited attention to their role in mediating affective and value formation. Addressing this limitation, the present study advances an integrative framework that synthesizes Barthesian semiotics with educational psychology to elucidate how linguistic signs operate in the production of meaning, the activation of affect, and the internalization of values. Methodologically, the study adopts an interpretive qualitative approach, employing a text-based analytical design grounded in library research. The corpus comprises 47 lines across 23 stanzas. Data are analyzed using Barthes’ two-order signification model (denotation and connotation/myth), complemented by a psychopedagogical lens that foregrounds affective activation, symbolic identification, and value internalization. The findings demonstrate that the dominant signs construct a multilayered system of religious meaning. These meanings are articulated through representations of reverence for the Prophet Muhammad and through the cultivation of affective and moral orientations, including respect, emotional attachment, spiritual aspiration, and transcendental awareness. The semiotic configuration operates as a symbolic mechanism that facilitates value internalization via emotional resonance and linguistic repetition. Theoretically, this study contributes an integrative semiotic–psychopedagogical model that extends semiotic inquiry into the domain of affective learning. Pedagogically, the findings suggest that Mahllul Qiyam can be effectively developed as interpretive instructional material to foster symbolic literacy, empathy, and character formation through reflective, value-oriented language learning practices.